Introduction - Sarkin, Jeremy (2022)
This article introduces the Special Section dealing with conflict related missing persons in Armenia, Azerbaijan, and Georgia. It examines the context to the conflicts in the region and brings to the fore the fact that the breakup of the Soviet Union has had a massive legacy in terms of the conflicts it spawned, over identity matters and various territorial claims, and how that vestige lingers today. The article examines why the three countries are useful to analyse comparatively, what we can learn from them and how these issues are also reflective of the democratic and human rights status in each. This article ends by discussing the general problems relating to missing persons in the three countries, and why the law and the processes to deal with missing persons in these and many other countries around the world need to be reformed. The focus of each of the three country articles is then more inward-looking. They explore the situation in each country concerning missing persons, the institutions that have been established to deal with those matters, the laws that deal with missing persons, and what is needed to make progress on all the issues relating to missing persons.